Fruit flies (Diptera: Teprithidae) and their parasitoid (Hymenoptera: Braconidae) species from registered snake fruit production during early rainy and dry seasons in the Special Region of Yogyakarta, Indonesia - Oka Dwi Handaru; Witjaksono Witjaksono; Dinta Dewi Arum; Kuwat Triyana; Suputa Suputa (Journal of Entomological and Acarological Research)
Exportation of snake fruit from Indonesia to China, Australia, and New Zealand has been hindered due to fruit fly infestations (Diptera: Teprithidae). The goal of this study was to identify fruit flies and their parasitoid species from registered snake fruit productions in Turi, Sleman, that have reached packaging houses during early rainy and dry seasons. Fruit fly species were morphologically identified from collected rejected or damaged snake fruit. Parasitization was calculated by dividing the number of emerging parasitoid species by the total number of parasitoid and fruit fly individuals. The population of fruit flies and parasitoids was then compared to climatic data. Female fruit flies that emerged from snake fruit possessed spots on their front preapical femur, concluding that these species were Bactrocera carambolae. The average fruit fly that emerged per fruit was 16.5 individuals. Only one parasitoid species emerged and possessed notauli on mesonotum that elongated to the center and petiole and longitudinal metasomal tergum 2, implying that this parasitoid species was Fopius arisanus with an average population of 5.71 individuals with a parasitization percentage of 26.86%. Results from this research concluded that the fruit fly species collected from registered snake fruit productions in Turi, Sleman, during the early rainy season and dry season was Bactrocera carambolae with a low parasitization level by Fopius arisanus. This parasitization level may be affected by fruit fly density and climatic factors, such as humidity and rainfall.